2017
DOI: 10.1016/j.neuropharm.2016.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Pramipexole enhances disadvantageous decision-making: Lack of relation to changes in phasic dopamine release

Abstract: Pramipexole (PPX) is a high-affinity D2-like dopamine receptor agonist, used in the treatment of Parkinson’s disease (PD) and restless leg syndrome. Recent evidence indicates that PPX increases the risk of problem gambling and impulse-control disorders in vulnerable patients. Although the molecular bases of these complications remain unclear, several authors have theorized that PPX may increase risk propensity by activating presynaptic dopamine receptors in the mesolimbic system, resulting in the reduction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 51 publications
1
17
0
Order By: Relevance
“…Onset is difficult to verify in humans as the clinical manifestations are not readily diagnosed until the ICSD becomes extreme. Fortunately, onset is clearly determined in dopamine agonist‐treated rats, with multiple reports showing that statistically significant enhancement in discounting tasks is obtained by 5–7 days of treatment (Rokosik & Napier, ; Holtz et al., ; Cocker et al., ; Pes et al., ; Tremblay et al., ). Behavior is normalized following reduction or termination of dopamine agonist therapy in both humans (Dodd et al., ; Hassan et al., ) and rats (Rokosik & Napier, ; Cocker et al., ).…”
Section: Functional Neuroanatomymentioning
confidence: 99%
See 1 more Smart Citation
“…Onset is difficult to verify in humans as the clinical manifestations are not readily diagnosed until the ICSD becomes extreme. Fortunately, onset is clearly determined in dopamine agonist‐treated rats, with multiple reports showing that statistically significant enhancement in discounting tasks is obtained by 5–7 days of treatment (Rokosik & Napier, ; Holtz et al., ; Cocker et al., ; Pes et al., ; Tremblay et al., ). Behavior is normalized following reduction or termination of dopamine agonist therapy in both humans (Dodd et al., ; Hassan et al., ) and rats (Rokosik & Napier, ; Cocker et al., ).…”
Section: Functional Neuroanatomymentioning
confidence: 99%
“…Given that mesocortical dopaminergic neurons are largely devoid of autoreceptors, and as the tonic firing of dopaminergic neurons is regulated by the ventral pallidum (Grace et al., ), these outcomes indicate that the adaptations to chronic pramipexole involve upregulated D3R pallidal control of dopamine cell firing to maintain tonic dopaminergic signaling in the cortex. Chronic pramipexole also reduces phasic release of dopamine in the nucleus accumbens (Pes et al., ). Both the prefrontal cortex and the nucleus accumbens are involved in risk‐based decision‐making (St Onge et al., , ), and these consequences would summate to drive disadvantageous choices.…”
Section: Functional Neuroanatomymentioning
confidence: 99%
“…In alignment with this idea, we recently showed that, in animal models, the effects of PPX on risky decision making were not based on modifications of dopamine release but were likely related to changes in downstream signaling of postsynaptic dopamine receptors. [36] It is also possible that ICDs in PD patients may feature specific characteristics secondary to the neurodegenerative condition, such as modifications of dopamine signaling in the ventral striatum secondary to hypofunction of the mesolimbic system in vulnerable PD patients. In support of this idea, recent studies have documented that dopaminergic deficits in the projections from the ventral tegmental area to the nucleus accumbens may be a critical predisposing factor to PPX/ROP-associated ICDs in PD.…”
Section: Discussionmentioning
confidence: 99%
“…In this perspective, our group recently developed a rat model of probability discounting specifically optimized to capture the increase in probability discounting following PPX treatment. [36] Supporting information S1 Table. ICD 9/10 -CM codes by mental disorder type. (DOCX)…”
Section: Discussionmentioning
confidence: 99%
“…This amphetamine-induced increase of risky decision during the probability discounting task is likely driven by activation of D1 and D2 receptors in different terminal regions (St. Onge 25 and Floresco, 2009;St. Onge et al, 2011;Stopper et al, 2013;Pes et al, 2017). However, the ability of amphetamine to alter risky choices was not observed in GDX rats relative to those with intact gonads.…”
mentioning
confidence: 99%